2009
DOI: 10.3200/joer.102.6.427-442
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a Conceptual Model-Based Approach to Teaching Situated Word Problems

Abstract: The authors explored the effects of teaching conceptual model-based problem-solving instruction on students' ability to solve problems in various situations. Participants were 3 4th-and 5th-grade students with or at risk for mathematics disabilities. The authors used an adapted multiple-probe across-participants design to assess the functional relation between the intervention and the students' problem-solving performance. The results indicate that the intervention improved students' performance on researcherd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 36 publications
(33 reference statements)
3
39
0
1
Order By: Relevance
“…Within the mathematics education and special education research communities, there is growing evidence about the effectiveness of SBI in supporting students' learning of word problem solving, particularly in arithmetic (e.g., Fuchs et al, 2009;Fuchs, Seethaler, et al, 2008, Fuchs et al, 2010Fuson & Willis, 1989;Jitendra et al, 2007;Lewis, 1989;Willis & Fuson, 1988) and ratio/proportion word problem solving (e.g., Jitendra et al, 2009;Xin, 2008;Xin et al, 2005;Xin, Wiles, & Lin, 2008;Xin & Zhang, 2009). However, other studies have indicated…”
Section: Discussionmentioning
confidence: 99%
“…Within the mathematics education and special education research communities, there is growing evidence about the effectiveness of SBI in supporting students' learning of word problem solving, particularly in arithmetic (e.g., Fuchs et al, 2009;Fuchs, Seethaler, et al, 2008, Fuchs et al, 2010Fuson & Willis, 1989;Jitendra et al, 2007;Lewis, 1989;Willis & Fuson, 1988) and ratio/proportion word problem solving (e.g., Jitendra et al, 2009;Xin, 2008;Xin et al, 2005;Xin, Wiles, & Lin, 2008;Xin & Zhang, 2009). However, other studies have indicated…”
Section: Discussionmentioning
confidence: 99%
“…The results of preliminary studies that evaluated COMPS using single-subject design (Kazdin, 1982) indicate that there is a functional relationship between the intervention and students' improved performance on researcher-designed criterion tests that involve simple addition, subtraction, multiplication, and division problems (e.g., Xin, Wiles, & Lin, 2008) and on problems involving irrelevant information or multiple steps (e.g., Xin & Zhang, 2009). The results also show that students improved their prealgebra concept and skills after the COMPS instruction.…”
Section: Conceptual Model-based Problem Solvingmentioning
confidence: 98%
“…In addition, due to the large numbers involved in the problems, simply replying on mental mathematics or "guess and check" may not be helpful in solving the problems. Cronbach's alpha of the COMPS test was .86, and the alternate form reliability was .85 (Xin & Zhang, 2009). Each item was worth a total of one point; the percentage of problems solved correctly on each test was calculated as the total points earned divided by the total possible points.…”
Section: Data Sourcesmentioning
confidence: 99%
“…To promote generalized problem solving skills, it is important that, following the concrete or semiconcrete modeling stage, students are provided with sufficient opportunities to directly apply abstract mathematical models (e.g., UR X # of Units D Product) for word problem representation. This requires systematic programming, which may involve strategically sampling a range of real-world contextualized problems, in order for students to conceptually understand each of the elements (e.g., unit rate) in the model equation (UR X # of Units D Product) and therefore reconstruct the mathematical model at the abstract level (Wagner, 2006;Xin & Zhang, 2009). Eventually, students should be able to use the model equation to solve not only problems with product as the unknown, but also problems with the factor as the unknown by directly applying the operation of division.…”
Section: Cognitive Levels Of Operation and Performance On Solving Conmentioning
confidence: 99%